Bicomponent electrospun scaffolds to design extracellular matrix tissue analogs. (2nd January 2016) - Guarino, Vincenzo; Cirillo, Valentina; Ambrosio, Luigi
Abstract : In the last decade, bicomponent fibers have been proposed to fabricate bio-inspired systems for tissue repair, regenerative medicine, medical healthcare and clinical applications. In comparison with monocomponent fibers, key advantage concerns their ability of self-adapting to the physiological conditions through an extended pattern of signals – morphological, chemical and physical ones – confined at the single fiber level. Hydrophobic/hydrophilic phases may be variously organized by tuneable processing modes (i.e., blending, core/shell, interweaving) thus offering different benefits in terms of biological activity, fluid sorption and molecular transport properties (first generation). The possibility to efficiently graft cell-adhesive proteins and peptide sequences onto the fiber surface mediated by spacers or impregnating hydrogels allows to trigger cell late activities by a controlled and sustained release in vitro of specific biomolecules (i.e., morphogens, growth factors). Here, we introduce an overview of current approaches based on bicomponent fiber use as extra cellular matrix analogs with cell-instructive functions and hierarchal organization of living tissues.